Gouty Arthritis with Massive Tophaceous Deposits Involving Bilateral Metatarsophalangeal Joints, Surgical Treatment with Excision and Reconstruction - A Case Report - Janardhana Aithala P; Dinesh Kumar Shetty (Journal of Orthopaedic Case Reports)
Introduction: Gout is characterized by the deposition of monosodium urate crystals and the formation of tophaceous deposits, which can lead to arthritis and bony erosions. While bony erosions in gouty arthritis are common, massive erosions of bone with the destruction of complete bone are rarely described. Case Report: We report a case of gouty arthritis with bilateral first metatarsophalangeal (MTP) joint involvement with bone erosion involving adjacent bones. Both sides were treated by surgical treatment with the excision of entire tophaceous deposits, the first MTP joint and the adjacent involved bones followed by reconstruction using interposition grafts. The patient was able to walk comfortably at the end of 6 months, with good cosmetic correction and healing of the wound. Conclusion: Surgical excision and reconstruction with intercalary graft for a massive tophaceous deposit around the first MTP joint can give satisfactory results.